Knowledge and the Prediction of Behavior: The Role of Information Accuracy in the Theory of Planned Behavior - Ajzen, Icek; Joyce, Nicholas; Sheikh, Sana; Cote, Nicole Gilbert (Basic and applied social psychology, 2011)
The results of the present research question the common assumption that being well informed is a prerequisite for effective action to produce desired outcomes. In Study 1 (N = 79), environmental knowledge had no effect on energy conservation, and in Study 2 (N = 79), alcohol knowledge was unrelated to drinking behavior. Such disappointing correlations may result from an inappropriate focus on accuracy of information at the expense of its relevance to and support for the behavior. Study 3 (N = 85) obtained a positive correlation between knowledge and pro-Muslim behavior, but Study 4 (N = 89) confirmed the proposition that this correlation arose because responses on the knowledge test reflected underlying attitudes. Study 4 also showed that the correlation could become positive or negative by appropriate selection of questions for the knowledge test. The theory of planned behavior (Ajzen, 1991 ), with its focus on specific actions, predicted intentions and behavior in all four studies.